Factors Associated with Incidence of Stunting in Toddlers at Loang Health Center Lembata Regency - Belutowe, Oktaviana; Littik, Serlie K.A.; Hinga, Indrianti A. Tedju (Faculty of Public Health, Nusa Cendana University, 2022)
Stunting is a form of chronic malnutrition which is characterized by an indicator of height according to age.The prevalence of stunting under five in Indonesia reaches 36.4% and the province of NTT is at the top.This study aims to determine the factors associated with the incidence of stunting in toddlers in the Loang Health Center Work Area, Nagawutun District, Lembata Regency.The type of research used is observational analytic research with a cross sectional study design.The sample in this study was 89 toddlers who were taken by means of simple random sampling technique.The data analysis used was univariate and bivariate analysis with chi square statistical test.The results of this study indicate that the factors associated with the incidence of stunting are the level of energy adequacy (95% CI=5,130-41,692; p=0,000), the level of protein adequacy (95% CI=7,668-74,193; p=0,000), feeding practices (95% CI=1,212-7,117; p=0,028), while the factors that are not related to the incidence of stunting are a history of disease. infection (p=0,342), practice of environmental hygiene and sanitation (p=0,161), care for sick children (p=0,845).From the results of this study, it is hoped that health workers can provide counseling about balanced nutrition to prevent stunting from an early age in mothers of toddlers so that the information obtained during counseling can be remembered and practiced properly.